Analysis of the performance of linear Fresnel collectors: Encapsulated vs. evacuated tubes. (April 2018) - Cagnoli, M.; Mazzei, D.; Procopio, M.; Russo, V.; Savoldi, L.; Zanino, R.
Highlights: The performance of a linear Fresnel collector is determined numerically. Two receiver configurations are compared (encapsulated vs evacuated tube). A ray tracing code is used to determine the absorbed heat flux distribution. CFD models are used to estimate the heat losses in different wind and sun conditions. The annual efficiency gain obtained using the evacuated tube is ∼10%. Abstract: In order to reduce the cost of the produced electricity, the Linear Fresnel Collector (LFC) system is a promising Concentrated Solar Power (CSP) technology. In this paper a detailed study is conducted aimed at the assessment of the heat losses from the receiver of a real 1 MWe pilot plant based on the Fresnel collector and cooled with a thermal oil. The receiver unit, which consists of an absorber tube and a compound parabolic concentrator (CPC), is investigated numerically in order to determine the receiver performance in different wind directions. Two receiver configurations are analyzed: a simply encapsulated one and an evacuated one. In the latter case, high vacuum conditions are reached in the gap between the absorber tube and the glass cover, whereas in the former case, air at ambient pressure fills the gap. The spatial distribution of the heat flux absorbed by the absorber tube and by the glass cover is determined by means of an optical analysis, conducted with the Monte Carlo based open-source ray-tracing tool Tonatiuh, and it is the driver of the ensuing thermal fluid dynamic analysis. A reference operation condition is studied in detail by means of a 1D model that solves the energy balance for the coolant along the entire length of the receiver. The characterization of the 1D model requires an accurate, multi-dimensional computational fluid dynamic (CFD) analysis, based on the commercial STAR-CCM+ code, which aims at determining the useful heat transferred to the coolant and the convective and radiative heat losses as a function of the oil temperature. A 2D CFD model is used to simulate the thermal behavior of the receiver at different locations along its axis in case of no wind or wind blowing across the collector axis. A 3D CFD model is adopted to study the impact of the wind blowing along the collector axis. The external air is considered in the computational domain in both CFD models, to be able to accurately assess the convective share of the heat losses. At the end, the oil temperature profile along the receiver tube, as well as the heat losses and the thermal efficiency trends, are presented and discussed. The 2D model is also exploited to perform an annual analysis, varying the solar flux and the sun position, but considering just a single wind direction. The results of our analysis indicate that the benefit of using an evacuated tube depends on the heat absorbed on the linear receiver, which depends in turn on the solar flux and on the sun position. The annual-based performance improvement obtained using an evacuated tube is not dramatic, due to the relatively low temperatures of the receiver. Moreover, this analysis also concludes that the receiver performance is only slightly affected by the wind direction and intensity up to ∼ 4 m/s, due to the presence of the CPC that protects the receiver from the external air stream.